Immunoglobulin Mutational Status Detected through Single-Round Amplification of Partial V(H) Region Represents a Good Prognostic Marker for Clinical Outcome in Chronic Lymphocytic Leukemia - Marasca, Roberto (American Society for Investigative Pathology, 2005)
The immunoglobulin (Ig) mutational status in B-cell chronic lymphocytic leukemia (CLL) distinguishes two subsets of patients with different prognosis. Ig status detection is commonly performed with a panel of V(H) family-specific primers. Although this method detects clonal VDJ rearrangement in virtually all cases, it is technically cumbersome and therefore not widely used clinically. Here, we describe a simple and rapid method to establish the mutational status of IgV(H) in CLL. The method is based on a consensus V(H) FR2 primer, used in both polymerase chain reaction (PCR) and sequencing reactions. Overall, monoclonal B-cell populations were detected in 163 of 189 CLL patients (86%). The prognostic value of IgV(H) mutational status was then evaluated by analyzing survival in 146 CLL cases using different V(H) homology cutoffs. CLL prognostic groups were best separated by the classical 98% cutoff: median survival was 127 and 206 months in unmutated and mutated CLL cases, respectively (P = 0.0023). V(H) FR2 consensus and V(H) family PCR were compared in 41 cases, correctly assigning all cases by both methods. Therefore, we suggest a sequential strategy to detect immunoglobulin mutational status in CLL patients by first using the approach described in this study followed by alternative V(H) family-specific PCRs for negative cases.